Exploring the Role of Shadow Teachers in the Implementation of Education in Inclusive Primary Schools in Surakarta City - Yudhani, Ardheila Setya; Fauziati, Endang; Minsih, M; Rahmawati, Laili Etika (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to explore the role of shadow teachers in the implementation of inclusive education in primary schools, with a particular focus on SD Negeri 1 Pajang, Surakarta. The research addresses how shadow teachers contribute to supporting students with special needs in regular classrooms. Methodology: A qualitative research approach was employed, using data collection techniques such as direct observation, in-depth interviews with shadow teachers, class teachers, and school principals, along with interactive data analysis to gain comprehensive insights into inclusive educational practices. Results: Findings indicate that shadow teachers play a pivotal role in adapting learning materials, managing student behavior, and collaborating with class teachers to create inclusive learning environments. Despite their significant contribution, challenges persist, including the limited availability of shadow teachers and the lack of specialized training programs to enhance their effectiveness. Applications/Originality/Value: This study contributes original insights into the practical strategies used by shadow teachers to overcome inclusive education barriers. It also offers valuable input for policymakers and educational institutions to strengthen the support system for shadow teachers, thereby improving the overall quality of inclusive education in Indonesia.